Plasmas for Treating Cancer: Opportunities for Adaptive and Self-Adaptive Approaches. Issue 6 (June 2018) - Keidar, Michael; Yan, Dayun; Beilis, Isak I.; Trink, Barry; Sherman, Jonathan H.
Abstract : Plasma is an ionized gas that is typically formed under high-temperature laboratory conditions. Recent progress in atmospheric plasmas has led to cold atmospheric plasma (CAP) devices with ion temperatures close to room temperature. The unique chemical and physical properties of CAP have led to its use in various biomedical applications including cancer therapy. CAP exhibits a spontaneous transition from a spatially homogeneous state to a modifiable pattern that is subject to self-organization. In this Opinion article, we discuss some new applications for plasma in cancer therapy based on plasma self-organization, which enables adaptive features in plasma-based therapeutic systems. Highlights: Cold atmospheric plasmas (CAPs) are ionized gases with ion temperatures close to room temperature. CAPs have unique chemical and physical properties, such as reactive species, charges, and an electric field; their remarkable anticancer capacity has been demonstrated with dozens of cancer cell lines in vitro and with mouse models in vivo . Self-organization is a process of spontaneous transition from a homogeneous state to a regular pattern or a transition between different patterns. Self-organization in plasmas could lead to the formation of coherent structures. These coherent structures can modulate plasma chemistry and composition, which could be utilized for an adaptive plasma device concept. The adaptive plasma approach is based on the ability to read the cellular response to CAP in real time and modify the composition and power of the plasma via a feedback mechanism.